2023
DOI: 10.1139/cjps-2022-0197
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the effects of seed treatments on the economically optimal seeding rate of conventional soybean in Atlantic Canada

Abstract: Soybean seeding rates in the cool growing environment of Atlantic Canada are much higher than other regions impacting economic return. Recent studies across North America have suggested that soybean seeding rates can be lowered to maximize profitability. Seed treatments have been shown to improve abiotic stress tolerance and may be another mechanism to reduce seeding rates. Therefore, the objectives of the present study were to (i) determine the economically optimal seeding rate (EOSR) for conventional soybean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Cross-pathogenicity among different crops can limit the efficacy of crop rotation in controlling Fusarium diseases [9,54]. As such, seed treatments are widely applied in North America to enhance seedling emergence and provide protection against soilborne pathogens on soybean [59][60][61]. Studies of fungicides and biocontrol agents as soybean seed treatments have also reported potential efficacy against single species of Fusarium under controlled conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Cross-pathogenicity among different crops can limit the efficacy of crop rotation in controlling Fusarium diseases [9,54]. As such, seed treatments are widely applied in North America to enhance seedling emergence and provide protection against soilborne pathogens on soybean [59][60][61]. Studies of fungicides and biocontrol agents as soybean seed treatments have also reported potential efficacy against single species of Fusarium under controlled conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Crosspathogenicity among different crops can limit the efficacy of crop rotation in controlling Fusarium diseases [9,44]. As such, seed treatments are widely applied in North America to enhance seedling emergence and provide protection against soilborne pathogens of soybean [49][50][51]. Studies of fungicides and biocontrol agents as soybean seed treatments have also reported potential efficacy against single species of Fusarium under controlled conditions.…”
Section: Introductionmentioning
confidence: 99%